Pipeline for precise insoluble matrisome coverage in tissue extracellular matrices - Chen, Wei; Zhang, Wen; Zhang, Ning; Chen, Shuyan; Huang, Tao; You, Hong (Frontiers in Bioengineering and Biotechnology, 2023)
Extracellular matrix (ECM) is assembled by hundreds of proteins orchestrating tissue patterning and surrounding cell fates via the mechanical-biochemical feedback loop. Aberrant ECM protein production or assembly usually creates pathological niches eliciting lesions mainly including fibrogenesis and carcinogenesis. Yet our current knowledge about the pathophysiological ECM compositions and alterations in healthy or diseased tissues is limited since the methodology for precise insoluble matrisome coverage in ECM is a “bottle neck”. Our current study proposed an enhanced sodium dodecyl sulfonate (E-SDS) workflow for thorough tissue decellularization and an intact pipeline for accurate identification and quantification of ECM highly insoluble matrisome proteins. We tested this pipeline in nine mouse organs and highlighted the full landscape of insoluble matrisome proteins in the decellularized ECM (dECM) scaffolds. Typical experimental validations and mass spectrum (MS) analysis confirmed very little contamination of cellular debris remaining in the dECM scaffolds. Our current study will provide a low-cost, simple, reliable and effective pipeline for tissue insoluble matrisome analysis in the quest to comprehend ECM discovery proteomic studies.